ANTECEDENTS OF PHILANTHROPIC BEHAVIOR OF PEOPLE LIVING IN JABODETABEK DURING COVID-19 PANDEMIC - Ida Faridatul Faridatul Hasanah; Donny Setiawan; Nining Nurhasanah (Sekolah Tinggi Ekonomi Islam (STEI) SEBI, 2020)
This study aims to examine the antecedents of the philanthropic behavior in the Jabodetabek community in the era COVID-19 pandemic. This type of research is a descriptive qualitative study consisting of 2 (two) variables used, namely exogenous and endogenous. The population in this study is the Jabodetabek community with 400 samples of respondents. The data analysis method used is the partial least squares structural equation modeling (SEM-PLS) method with the help of SmartPLS 3.0 software. The results of this study indicate that: (1) individual factors on philanthropic behavior in this study do not have a positive and significant effect, (2) organization factors on philanthropic behavior in this study have a positive and significant effect, (3) social factors on philanthropic behavior in this study. This has no positive and significant effect.